(untitled) (Profetik: Jurnal Komunikasi, 2024)
The development and practice of journalism are mainly determined by the availability of information and communication technology. Internet-based technology has transformed all lines of journalism. Journalism convergence is not only a trend, but also a necessity in the contemporary media industry. There are three types of journalism convergence, namely newsroom, newsgathering, and content. In newsroom convergence, journalists from different platforms work together in one news production room and carry out their tasks in accordance with their media. Newsgathering convergence requires journalists to multitask, while content convergence or news content means that news is displayed in the form of multimedia content that combines texts, images, audio and others. This study aims to describe and analyze the practice of journalism convergence in Media Group Network and Mahaka Media. Using a qualitative approach, the researchers conduct observation, interview, and literature review as data collection techniques. This study finds that Media Group Network and Mahaka Media have already applied these three journalism convergence models (newsroom, newsgathering, and content). Media Group Network and Mahaka Media have been continuously and consistently applying those three aspects of journalism convergence. However, there are some differences in the journalism convergence process in Media Group Network and Mahaka Media, namely the code of ethics and training for journalists. Another difference is that Mahaka Media provides print on demand for its readers, while Media Group Network has broad coverage on journalism convergence through free to air television, Metro TV